THE INTERACTIVE TESTING IN THE ENGLISH FOR SPECIFIC PURPOSES TEACHING IN NON-LINGUISTIC UNIVERSITIES - Olena Hryshyna (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
In the paper the author gives a thorough analysis of the effective tools for the control organization in terms of the recent researches in the English for specific purposes testing methodology. The writer proposes the effective technology of the reading competency measurement covering the methods and techniques of the test administration including the criteria and quality characteristics definition. The research gives the sound articulation of the test quality characteristics alongside with the outlined test task design requirements. The examples of the original communicative professional test tasks give an overall picture of the testing domain to be developed. The objectives outlined give the reader an understanding of the test structure evaluation and processing the output data. The research gives a possibility to obtain a practically ideal tool for measuring the study achievements in reading competency acquisition of the technical university students. Moreover, the research highlights the learning outcomes to be envisaged beforehand as the target skills the students-future engineers are to acquire. The paper investigates the impact of the test characteristics and qualities on the test task construction in terms of the learning and testing purposes interaction. The research focuses on the test task development requirements as a dominant creative force in a testing development, organization and administration. Being sufficiently useful, criteria bring a sound functionality in the test task and test items construction. The structure of the communicative real life situations in foreign language reading where the future technical specialists are to apply their certain reading skills for their academic purposes is elaborated and introduced in the paper.